Validation Study of Intangible Business Relationship Value Measurement - Zhang, Annie Liqin (Auckland University of Technology, 2004)
Both marketing researchers and practitioners realise that having customer relationships that enhance a firm's competitive advantage is an important strategic issue and that there is a need for relationship value measurement. But the research on relationship value measurement is limited, especially from a seller's perspective, despite numerous calls for it. The reason for the limited research might be that the nature of customer relationships is complex, largely intangible, and long-term oriented. Baxter and Matear's (2004) study directly addresses the issue of the measurement of the intangible part of the value of a business-to-business relationship from a seller's perspective. Synthesising an intellectual capital model into the relationship marketing literature, Baxter and Matear (2004) propose an intangible relationship value (IRV) model for assessing the value of the intangible part of the resources that sellers gain through their relationships with their business buyers. The IRV model has been empirically tested and supported in New Zealand's manufacturing industry. The current study replicated Baxter and Matear's (2004) study in order to further assess the validity of the IRV model and its scales. Exploratory factor analysis was used first to identify the dimensionality of the IRV. Then the four aspects of construct validity - reliability, and convergent, discriminant, and nomological validities - were examined. The exploratory factor analysis of the focal relationship value items in the questionnaire found six first-order dimensions of the IRV. As expected, these six first-order value dimensions are the same as in the Baxter and Matear (2004) study: competence, attitude, intellectual agility, relationships, organisation, and renewal and development. Further exploratory factor analysis of the summated scales of these six first-order values found two higher-order value dimensions: the human intangible value dimension and the structural intangible value dimension. Thus the dimensionality of the IRV model is supported in the current study. The exploratory factor analysis retained 36 out of the initial 42 measures developed by Baxter and Matear (2004). These 36 retained measures include 20 of the 22 measures in Baxter and Matear's (2004) final purified scales. The validity of these 36 measures was then further investigated. The reliability examination found that the measurements of the six first-order IRV constructs are reliable in the current study. Evidence was also found for the convergent and discriminant validities in the measurements of the human and structural intangible value, the convergent validity in the measurement of the IRV, and the nomological validity of the IRV construct. Thus, the 36 measures retained in the final results of the current study are valid for the respondents in the current study. The findings suggest that Baxter and Matear's (2004) intellectual capital approach to measuring IRV is appropriate. It has potentially provided a way to assess intangible value in relationships. Based on the dimensions and the measures provided by the IRV model, sellers can systematically assess the potential IRV of their current and potential customer relationships, and make their strategic decisions on how to manage these customer relationships accordingly.
Keywords: Value measurement; Intangible value; Relationship value; Business